Implementasi Multiple Intelegences dalam Pendidikan Anak Usia Dini - Sri Widiyati (CV. Syntax Corporation Indonesia, 2021)
Intelligence is the ability to solve problems and create creativity. The potential intelligence of a child and the basic character of a child are formed at this time. This research aims to explore the Theory of Multiple Intelligence (Theory of Compound Intelligence). Using theoritical research methods or often referred to as literature research or library research, not an empirical research. All data is obtained through various articles in various journals, books, and other print media so that theoretical studies are more in-depth. . According to Gardner, intelligence is an ability to solve problems faced, in his life, the ability to develop new problems to be solved, and the ability to make something or do something useful in his life, then The nine intelligences are liguistic verbal intelligence, mathematical logic intelligence, visual spatial intelligence, kinesthetic-physical intelligence, musical intelligence, interpersonal intelligence, intrapersonal intelligence, naturalist intelligence, and existential intelligence